Pendekatan Etnomatematika Meningkatkan Kemampuan Matematis Siswa - Winanda Marito (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to identify research that represents ethnomathematics to improve students' mathematical abilities in Indonesia. This type of research is a literature study. The data obtained was then analyzed through three stages, namely organizing, synthesizing, and identifying. organizing that is compiling the literature that will be used. A literature review is first carried out at this stage to be grouped so that it is relevant to the problem. At this stage, the writer looks for ideas, goals and conclusions from several literatures, starting with reading abstracts, introductions, methods and discussions and grouping the four literatures originating from Sinta's accredited nationally accredited journals. Second, synthesis, namely organizing the data obtained in the first stage into a summary by looking for links between documents, so that they become a coherent whole. Third, identification, namely identifying key data in the literature. The results of the research show that local wisdom or culture can be used as a medium for learning mathematics, and based on existing literature that an ethnomathematics approach can improve mathematical abilities